(untitled) (Swiss Medical Weekly, 2025)
INTRODUCTION: Currently, approved disease-specific therapies for patients with immunoglobulin (Ig) A nephropathy in Switzerland are scarce. According to the 2024 KDIGO guidelines, current treatments focus on reducing proteinuria and nephron loss using nephroprotective regimens consisting of renin-angiotensin system blockade, the use of sodium-glucose cotransporter-2 (SGLT-2) inhibitors, and the dual endothelin angiotensin receptor antagonist sparsentan. Systemic glucocorticoids and a targeted-release formulation of budesonide are other therapeutic options to reduce IgA nephropathy-specific drivers of nephron loss. However, their use has been associated with adverse effects, even with targeted-release budesonide, and the benefit of these therapies remains to be weighed against the risk of treatment-emergent toxicity. This highlights the ongoing need to identify more effective and safer therapies for the treatment of IgA nephropathy. In the last few years, increasing understanding of the pathogenetic role of alternative complement pathway dysregulation in the onset and progression of IgA nephropathy has led to the development of new complement-targeting therapies. Iptacopan is an oral inhibitor of complement factor B that effectively blocks the alternative complement pathway. CASE PRESENTATION: We report the successful treatment of a 40-year-old female patient suffering from IgA nephropathy with iptacopan. In this patient, despite maximum tolerated renin-angiotensin system blockade and fully dosed SGLT-2 inhibitor administration, we failed to achieve the desired reduction in proteinuria to <0.5 g/day. Proteinuria persisted at a level of >1 g/day despite the goal of blood pressure ≤120/70 mm Hg being achieved. Impressively, within just two months after the initiation of iptacopan, we noted a reduction in proteinuria to 0.5 g/day, and after nearly six months, we reached our goal, with proteinuria at <0.3 g/day, a value continuing to the present day. Further, the medication was well-tolerated. CONCLUSION: To the best of our knowledge, our case report is the first in Switzerland to show that selective inhibition of the alternative complement pathway in IgA nephropathy results in significant and ongoing reduction of proteinuria after six months of therapy, supporting the innovative concept of targeting the alternative complement pathway with iptacopan to treat IgA nephropathy.